Removing the stigma of divorce: Happiness before and after remarriage - Sueheon Lee (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Many studies confirm that marriage does not have lasting effects on levels of happiness, whereas divorce induces serious, scarring effects through social stigma. However, few academic efforts have been made regarding how remarriage after divorce impacts the subjective well-being (SWB) of the divorced. Taking into consideration that remarriage often entails regaining social acceptance, this paper examines the possibly different patterns of happiness depending on marital order. Specifically, this longitudinal study uses the German Socio-Economic Panel (SOEP) data set in order to compare SWB trajectories around first and subsequent marriages. The results show that the remarried go through a significantly greater boost in happiness than the first-married during the transition phase. Moreover, while life satisfaction that increased in the years around the first marriage quickly returns to the initial baseline, remarriage generates a lasting increase. This paper provides a complementary perspective to existing researches on divorce and debates over the hedonic treadmill theory.
Keywords: 330; Remarriage; Subjective well-being; Life course; Social stigma